The role of NU’s for Indonesia: NU’s jihad resolution as an effort to preserve the unitary state of the Republic of Indonesia and religious moderation - Faizah, Rohmatul; Baedowi, Ahmad (Universitas Islam Nahdlatul Ulama Jepara, 2023)
The long struggle of the Indonesian people in breaking away from the shackles of imperialism cannot be separated from the role of Islamic figures. One of the struggles of Indonesian Muslims in fighting for independence was in the battle of November 10, 1945 in Surabaya, beginning with the Jihad Resolution KH. Hasyim Asy'ari who succeeded in building religious nationalism of the Indonesian nation. He holds moderate and tolerant teachings in order to strengthen the unity of the nation. One of the scholars figures whose national commitment is unquestionable is K.H. Hasyim Asy'ari. He is a scholars with a big name who was famous in his time. K.H. Hasyim Asy'ari is a representation of the character of a typical Indonesian scholars who is moderate and maintains local wisdom. In addition to having intellectual intelligence, he is also an organizer, educator, and even citizens who have high asceticism. This research included library research. This method collects data by understanding and studying theories from various related kinds of literature. The method of analysis uses content analysis and descriptive analysis. The results showed that the concept of moderate thinking KH Hasyim Asy'ari (Jihad Resolution) underlies the birth of the jihad resolution against the invaders to defend the Unitary Republic of Indonesia. Contextualization of Jihad Resolution initiated by K.H. Hasyim Asy'ari has a very broad dimension and influence, namely part of efforts to preserve the Unitary State of the Republic of Indonesia and moderation in religion